PENGEMBANGAN MODEL PEMBELAJARAN KEBENCANAAN BERBASIS KEWILAYAHAN DI TINGKAT SEKOLAH MENENGAH ATAS - Rahmawati; Zumrotin Nisa; Amalia Novarita (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2021)
The earthquake, tsunami and liquefaction incident on 28 September 2018 caused huge casualties. This research is a type of R&D research by following the ADDIE development up to stage 5, analysis, design, develop, implementation, and evaluation. The population were students and teachers in class XI Senior High School in Sigi Regency. Data collection techniques and instruments were carried out through tests and non-tests which included interviews, observations, questionnaires, validation instruments, knowledge test questions. The results of study indicate the feasibility of products that have been validated by experts is at a decent qualification, namely 80%. The learning equipment products were stated to be very practical by the teacher, 89.93% and practical by the students, namely 77.97% for the SETS learning and 75.50% for the practicality of the disaster mitigation and adaptation modules. The results of the effectiveness test were declared effective in the medium category with a score of 0.40.